M.M. Suárez, R. Torrealba, H. Vessuri (compiladores), Cambio social y urbanización en Venezuela, Monte Avila Editores, Caracas, 1983, 311 pp. - Hodara, Joseph (Estudios Demográficos y Urbanos, 1984)
M. M. Suárez, R. Torrealba, H. Vessuri (compiladores). Cambio social y urbanización en Venezuela, Monte Ávila Editores, Caracas, 1983.